Social inequalities in news consumption - Kalogeropoulos, A; Nielsen, R (Reuters Institute for the Study of Journalism, 2017)
The expansion of media choice during the past years often results in those who are most interested consume more news, whereas those who are less interested increasingly tune out of news (Prior, 2005). Research has also found that the choices individual news users make are related to their social status (Lindell, 2017). This factsheet focuses on social inequalities in news consumption in the UK to address the question of whether inequality is increasing as we move to a more digital media environment. Based on survey data on offline and online news consumption and taking into account individual differences in social grade, we find that a) news consumption is more unequally distributed in the UK than income is b) online news consumption is more unequally distributed than offline news consumption c) there is greater social inequality in online news consumption than in offline news consumption.